Qualitative Determination of Human Chorionic Gonadotropin in Vaginal Washings for the Early Diagnosis of Premature Rupture of Fetal Membranes - Camila Buziquia Dartibale; Nelson Shozo Uchimura; Luiz Nery; Angelita Polato Schumeish; Liza Yurie Teruya Uchimura; Rosangela Getirana Santana; Taqueco Teruya Uchimura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose This study aimed to evaluate and validate the qualitative human chorionic gonadotropin β subunit (β-hCG) test of the vaginal fluid washings of pregnant women with premature rupture of fetal membranes (PROM). Methods Cross-sectional study of pregnant women between gestational weeks 24 and 39 who underwent consultations in one of our institutions. They were divided into two groups: group A (pregnant women clinically diagnosed with PROM) and group B (pregnant women without loss of amniotic liquid). The patients were subjected to a vaginal fluid washing with 3 mL of saline solution, which was aspirated subsequently with the same syringe. The solution was immediately sent to the laboratory to perform the vaginal β-hCG test with cut-off points of 10 mIU/mL (β-hCG-10) and/or 25 mIU/mL (β-hCG-25). Results The β-hCG-10 test of the vaginal secretion was performed in 128 cases. The chi-squared test with Yates' correction showed a statistically significant difference between the 2 groups (p = 0.0225). The sensibility, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy parameters were 77.1%, 43.6%, 52.3%; 70.4%; and 58.6% respectively. The β-hCG-25 test of the vaginal washing was performed in 49 cases. The analysis by Fisher's exact test showed a statistically significant difference between the groups (p = 0.0175). The sensibility, specificity, PPV, NPV, and accuracy parameters were 44.4%, 87.1%, 66.6%; 72.9%; and 71.4% respectively. Conclusions The β-hCG-25 test showed better accuracy for the diagnosis of PROM, and can corroborate the early diagnosis of PROM because it is a simple and quick exam.